ANALYSIS OF ECONOMIC POTENCY IN AGRICULTURAL, FORESTRY AND FISHERY SECTOR OF JEMBER DISTRICT - Ahmad Rizani (Universitas Pendidikan Ganesha, 2018)
This study aims to examine the economic potential in the sector and sub-sector of agriculture, forestry and fishery of Jember Regency. In addition, this study also highlights and determines the leading sectors and sub-sectors in Jember Regency to provide an overview of superior economic activities that can be developed in increasing the economic potential in Jember District. The data used in this study is secondary data in the form of time series (time series) for 6 years from 2010 to 2015 Gross Regional Domestic Product (GRDP) of East Java Province, GRDP (Gross Regional Domestic Product) Jember District. The data was obtained from Central Bureau of Statistics (BPS) of East Java Province and Central Bureau of Statistics (BPS) of Jember Regency. Shift-Share, Location Quotient (LQ), and Growth Ratio Model (MRP). From the results of the research: (1) shift-share analysis shows that the economy of Jember Regency during 2010-2015 period increased by Rp2,412.3 billion. The performance improvement in Jember Regency can be seen from the sectors and sub-sectors of agriculture, forestry and fisheries; (2) based on the analysis of Quotient Location (LQ) of the sector and the leading sub-sector in Jember Regency there is 1 sector and 1 sub-sector with average LQ> 1 or potential sectors and subsectors namely agriculture, farming, hunting & agricultural services and plantation sub-sector; (3) Growth Ratio Model (MRP) analysis shows the dominant sectors of growth and subsector of plantation, sub-sector of agricultural and hunting services, forestry and logging sector, and fishery sector. Keywords: Economic Potential, Shift-Share, Quotient Location (LQ), Growth Ratio Model (MRP)